2010
DOI: 10.1111/j.1742-7843.2010.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Serum S100B Protein and Neuron‐Specific Enolase Levels of a Single Dose of Chlorpyrifos in Rats

Abstract: Organophosphate (OP) compounds are a large class of chemicals, many of which are used as pesticides. It is suggested that OPs specifically affect glia and neurons. Effects of acute exposure to chlorpyrifos (CPF), which is a common organophosphorus pesticide used worldwide, on neuron-specific enolase (NSE) and S100B levels in rat blood during 7 days were assessed. Rats were evaluated either before (0 hr) or 2, 12, 24, 48 and 168 hr (7 days) after injection of CPF (279 mg ⁄ kg, s.c.) or vehicle (peanut oil, 2 ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 57 publications
6
16
0
Order By: Relevance
“…As regard, serum S100B level at both admission and after 24hrs, this study revealed significant increase in its level in died patients than survived patients although, it cannot predict mortality. Bozkurt et al, (2010) reported that S100B level was elevated 2 h after exposure to chlorpyrifos in adult rats revealing usefulness of it in assessment of OP toxicity. Additionally, Yardan et al, (2013) detected that S100B level was significantly elevated in nonsurvivors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As regard, serum S100B level at both admission and after 24hrs, this study revealed significant increase in its level in died patients than survived patients although, it cannot predict mortality. Bozkurt et al, (2010) reported that S100B level was elevated 2 h after exposure to chlorpyrifos in adult rats revealing usefulness of it in assessment of OP toxicity. Additionally, Yardan et al, (2013) detected that S100B level was significantly elevated in nonsurvivors.…”
Section: Discussionmentioning
confidence: 99%
“…Schwann cells), and S-100BB (astroglial cells) (Bottiger et al, 2001). S100B is expressed mainly in astrocytes of the central nervous system (CNS) (Yardan et al, 2009;Bozkurt et al, 2010). S100B is an established peripheral biomarker of blood-brain-barrier permeability associated with various CNS injuries or degeneration such as traumatic cortical injury and cerebrovascular insults as well as in some psychiatric disorders (Rothermundt et al, 2003), cardiac arrest or surgery (Qiao et al, 2001;Caughlan et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Jaiswal and Verma [34][35][36] also reported that the most profound rat stress was the reduction of body weight after administration of chlorpyrifos. Studies conducted by [37][38][39] gave decreased body weights in rats treated with chlorpyrifos with no effects on physical or reflex development. This present study also revealed leucopenia in packed cell volume (PCV) which was apparently due to lymphopenia, neutropenia, and monocytopenia in the chlorpyrifos animal treated groups.…”
Section: Discussionmentioning
confidence: 99%
“…Stromal cell-derived factor-1 α (SDF-lα), one of the crucial signal molecules and landmarks of cell migration, was actually involved in triggering migration of Sca-1+ progenitor cells into the neointima by activating its receptor CXCR4 in the process of neointimal formation after vessel damage [20]. Considering the traits of common action of S100B and SDF-lα as inflammatory factors, S100B levels reached the peak at 2–6 h after tissue injury [21, 22], while SDF-lα expressions peaked 24 h after heart and vessel injury [23, 24], indicating that S100B could have a potential role in inducing SDF-lα expression in the injured vessels, and involving in the development of neointimal formation through SDF-lα signaling.…”
Section: Introductionmentioning
confidence: 99%